Fabrication and Characterization of Organoclay Reinforced Polyester Based Hybrid Nanocomposite Materials - Zaman, N.; Ahmed, S.; Sanaullah, M.; Rehman, A. U.; Shar, A. R.; Luhur, M. R. (Engineering, Technology & Applied Science Research, 2018)
Synthesis and characterization of polyester nanocomposites was conducted in order to fabricate hybrid composite materials of polyester/montmorillonite (MMT). Polyester based polymeric nanocomposite materials were synthesized by incorporating MMT nanoclay to produce polyester/MMT hybrid materials. Successful efforts were made to fabricate hybrid nanocomposite materials based on matrix (polyester based) and reinforcement (organoclay) through sonication at 6 and 12 hours. Synthesized nanocomposite polymers (polyester/MMT) showed different properties when compared to the properties of MMT and polyester, which confirmed the successful fabrication of the desired material. The finest incorporation of polyester with MMT was verified by UV-Visible spectrophotometer, Fourier tranform-infrared (FTIR) and scanning electron microscopy (SEM). The disappearance of the Si-O characteristic peak was observed in the FTIR spectrum justifying the fabrication of the desired composite materials. Colored SEM images were used to confirm the fine homogenous distribution of organoclay. Black SEM images showed the matrix and reinforcement together. SEM, FTIR and UV-Visible spectroscopic techniques were used to analyze polyester based nanocomposite materials and organoclay was found randomly distributed in the polymeric matrix whereas on the surface was observed to be mostly uniform.